AdipoRon’s Impact on Alzheimer’s Disease—A Systematic Review and Meta-Analysis - Barbalho, Sandra Maria; Laurindo, Lucas Fornari; de Oliveira Zanuso, Bárbara; da Silva, Rebeca Maria Siqueira; Gallerani Caglioni, Lívia; Nunes Junqueira de Moraes, Victor Bruno Fonseca; Fornari Laurindo, Lívia; Dogani Rodrigues, Victória; da Silva Camarinha Oliveira, Jéssica; Beluce, Maria Eduarda; Penteado Detregiachi, Cláudia Rucco; Barbalho Lamas, Caroline; et al. (MDPI, 2025)
Alzheimer’s disease (AD) remains a leading cause of cognitive decline and mortality worldwide, characterized by neurodegeneration, synaptic deficiencies, and neuroinflammation. Despite advancements in early detection, diagnosis, and treatment, AD presents substantial challenges due to its complex pathology, heterogeneity, and the limited efficacy of current therapies. Consequently, there is a pressing need for novel therapeutic agents to target the multifaceted aspects of AD pathology, enhance current treatments, and minimize adverse effects. AdipoRon, an adiponectin receptor agonist, has garnered interest for its potential neuroprotective effects, including reducing neuroinflammation, improving mitochondrial function, and mitigating tau hyperphosphorylation. This review aimed to evaluate the effects of AdipoRon-based adiponectin replacement therapy against AD, using a comprehensive approach grounded in the PICO framework—Population, Intervention, Comparison, and Outcomes. A total of six studies were reviewed, including in vitro and in vivo investigations examining AdipoRon’s impact on various AD models. These studies involved different cell lines and transgenic mouse models, assessing various outcomes such as cognitive function, neuroinflammation, tau phosphorylation, synaptic deficiencies, and relevant molecular pathways. By synthesizing data from these studies, our review thoroughly explains AdipoRon’s neuroprotective effects, mechanisms of action, and potential as a therapeutic agent for AD. This analysis aims to highlight the current state of knowledge, identify gaps in the research, and suggest directions for future studies and clinical applications.
Keywords: adiponectin; adiponectin receptor agonist; adiponectin replacement therapy; AdipoRon; Alzheimer’s disease; cognitive impairment; neurology; synaptic defects